The relationship between physical activity and subjective well-being in Chinese university students: the mediating roles of perceived health, social support and self-esteem - Liao, Tianzhi; Yin, Yujia; Hu, Xiaoyong; Tang, Saizhao; Shim, Yunsik (Frontiers in Sports and Active Living, 2023)
The intent of this paper is to understand the effect of Physical Activity on university students' Subjective Well-being and to explore whether Perceived Health, Social Support, and Selfesteem play roles as mediating variables. Methods: Self-reported data from 404 college students (147 males and 257 females) were analyzed using structural equation modeling (SEM). The relationships between the study variables were tested by mediation models and 5000 bootstrap samples using AMOS version 24. Results: (1) The six hypotheses were supported in the measurement model in the results (P<0.05). Physical Activity was related to Social Support, Perceived Health, and to Selfesteem; Social Support, Perceived Health, and Self-esteem were all related to Subjective Well-being. However, the direct positive effect of Physical Activity gradually decreased in the order of Selfesteem, Social Support, and Perceived Health. The direct effect of Perceived Health, Social Support, and Self-esteem on Subjective Well-being also decreased sequentially. (2) In the Structural Equation Model (χ²=825.451, p<0.001, df=455, CMIN/df=1.814, CFI=0.942, RMSEA=0.045), the three hypotheses of mediation were supported (P<0.05), showing positive indirect effects between Physical Activity and Subjective Well-being. Of the three mediating effects, Social Support and Self-esteem were not different, and the mediating effect of Perceived Health showed the largest impact. This indicates that Social Support, Perceived Health, and Self-esteem mediate the effects of Physical Activity, and Subjective Well-being regulation has positive indirect effects. Conclusion: This study demonstrates the importance of meeting the needs of Social Support, Perceived Health, and Selfesteem when designing interventions to promote college students' sports participation to enhance Subjective Well-being.